(untitled) (Faridpur Medical College Journal, 2011)
Haemodynamic stability is an integral and essential goal of any anaesthetic management plan. Laryngoscopy and intubation can cause striking changes in haemodynamics. Increase in blood pressure and heart rate occurs most commonly from reflex sympathetic and vagal discharge in response to laryngotracheal stimulation, which in turn leads to increased plasma norepinephrine concentration. This study was designed to compare efficacy of esmolol and lignocaine for attenuating haemodynamics response due to laryngoscopy and endotracheal intubation. The aim of this study was to compare the effects of Esmolol with that of Lignocaine to attenuate the detrimental rise in heart rate and blood pressure during laryngoscopy and tracheal intubation. One hundred and twenty adult patients randomized into group-L and group-E, were received lignocaine 1.5 mg/kg and Esmolol 1.5 mg/kg I.V. respectively. Heart rate and blood pressure in each minutes for the 10 minutes after intubation was recorded. Time span around intubation up to 4 minutes has been looked specifically to isolate the effect of the study drugs at the time of intubation. For statistical analysis Student’s ’t’ test was used for comparing means of quantitative data and chi-square test was used for qualitative data. Difference was considered statistically significant if p<0.05. The mean heart rate, systolic, diastolic, and mean blood pressure, and rate-pressure product before starting anesthesia were similar in group-L (Lignocaine group) and in group-E (Esmolol group) (p>0.05). The mean values of heart rate, systolic, diastolic, and mean blood pressure, and rate-pressure product at 2, 3 and 4 minutes after intubation were significantly lower in group-E than group-L (p<0.05). In conclusion, esmolol 1.5 mg/kg is superior to lignocaine (1.5 mg/kg) for attenuation of haemodynamic response to laryngoscopy and endotracheal intubation. Key words: Haemodynamics; heart rate; intubation; esmolol; lignocaine DOI: 10.3329/fmcj.v5i1.6810 Faridpur Med. Coll. J. 2010;5(1):25-28